Histone modifier gene mutations in peripheral T-cell lymphoma not otherwise specified - Ji, Meng-Meng (Haematologica, 2018)
Due to heterogeneous morphological and immunophenotypic features, approximately 50% of peripheral T-cell lymphomas are unclassifiable and categorized as peripheral T-cell lymphomas, not otherwise specified. These conditions have an aggressive course and poor clinical outcome. Identification of actionable biomarkers is urgently needed to develop better therapeutic strategies. Epigenetic alterations play a crucial role in tumor progression. Histone modifications, particularly methylation and acetylation, are generally involved in chromatin state regulation. Here we screened the core set of genes related to histone methylation (KMT2D, SETD2, KMT2A, KDM6A) and acetylation (EP300, CREBBP) and identified 59 somatic mutations in 45 of 125 (36.0%) patients with peripheral T-cell lymphomas, not otherwise specified. Histone modifier gene mutations were associated with inferior progression-free survival time of the patients, irrespective of chemotherapy regimens, but an increased response to the histone deacetylase inhibitor chidamide. In vitro, chidamide significantly inhibited the growth of EP300-mutated T-lymphoma cells and KMT2D-mutated T-lymphoma cells when combined with the hypomethylating agent decitabine. Mechanistically, decitabine acted synergistically with chidamide to enhance the interaction of KMT2D with transcription factor PU.1, regulated H3K4me-associated signaling pathways, and sensitized T-lymphoma cells to chidamide. In a xenograft KMT2D-mutated T-lymphoma model, dual treatment with chidamide and decitabine significantly retarded tumor growth and induced cell apoptosis through modulation of the KMT2D/H3K4me axis. Our work thus contributes to the understanding of aberrant histone modification in peripheral T-cell lymphomas, not otherwise specified and the stratification of a biological subset that can benefit from epigenetic treatment.